NEO-LIBERAL CLASS WAR AND HOBBESIAN STATE OF NATURE IN NIGERIA - IFEANYI UGWU JR. LEONARD; ARINZE VICTOR NWAWUBE; OMEH PAUL HEZEKIAH; MICHAEL I. UGWUEZE (International Studies Journal, 2025)
Evidently, divergent literary exploration has attributed the Hobbesian state of Nature in Nigeria to various reasons like tribalism, mixed cultural heritage, corruption, among others.  This study microscopes Neo liberalism as the major political and social melee affecting the country. The research investigates how neo-liberalism in the feature of global capitalism and imperialism forms an extreme division between top elite 1% and bottom struggling 99% which results in huge inequality while promoting corruption and weakening institutions. The research bases itself on neo-liberal theory to disclose how elite groups achieve resource control and economic instability while destroying national sovereignty and ethics. A qualitative study of secondary reports and economic indices and journal entries confirms that Nigeria experienced 32.5% inflation in 2024 alongside a 76–77% corruption index between 2022 and 2025 and 735 mass abductions and 24,720 recorded rapes from 2023 to date. The privatization process benefits wealthy individuals while electricity reaches only 30% of people and homelessness affects more than 4.5 to 5 million people in the country. The research finds that Nigeria became a Hobbesian state because neo-liberal policies increased class conflicts while demanding judicial changes alongside fair resource distribution and economic expansion to stop the development of permanent chaos. The research calls for rebuilding Nigeria’s approach to fairness and stability by confronting the world's current economic model of liberalism.